Pengaruh Loyalitas, Prestasi Kerja Dan Senioritas Terhadap Promosi Jabatan Pegawai Pada Kantor Balai Guru Penggerak (BGP) Provinsi Aceh - Cut Fandriani; Lukman T. Ibrahim; Isthafan Najmi (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
Employee loyalty, work performance and seniority are basic information that can be used as a guide for agencies to determine which employees are worthy of being promoted to higher positions. In carrying out job promotions, agencies use work performance as one of the determining factors, where employees who have good work performance will also have a high chance of being promoted. Before a promotion is held, the leadership will carry out an objective assessment of work performance. The purpose of this research is to determine the magnitude of the influence of loyalty, work performance and seniority on promotion of employee positions at the Aceh Province Teacher Mobilization Center (BGP) Office. Based on the Cronbach alpha value for the Loyalty variable (X1) it is 0.677, the Work Performance variable (X2) is 0.690, the Seniority variable (X3) is 0.646 and Position Promotion (Y) is 0.692. The results of the t test (partial) regarding the loyalty variable value tcount>ttable (1.752>1.678), with a significant value of 0.000 <0.05. This means that it influences employee promotions. The results of the t test (partial) regarding the work performance variable were tcount>ttable (2.320>1.678), with a significant value of 0.000 <0.05. This means that it influences employee promotions. The results of the t test (partial) regarding the seniority variable are tcount>ttable (2.044>1.678), with a significant value of 0.000 <0.05. This means that it has an effect on employee promotion and based on the results of the f test (simultaneous) it concludes that the Fcount>Ftable value is (2.995>2.810), with a significant value of 0.000 <0.05. This means that loyalty, work performance and seniority influence the promotion of employee positions at the Aceh Province Teacher Mobilization Center (BGP) Office.